The future of oncology pharmacy: European Conference of Oncology Pharmacy 2018. Issue 3 (July 2019) - Meier, Klaus; Astier, Alain; Boşnak, Ahmet Sami; Goněc, Roman
Abstract : Abstract: The way we treat cancer is changing. Scientific and technological advances such as tumour profiling, 'big data, ' and an increasing number of targeted therapies and combination regimens will result in a paradigm shift away from a 'one-size-fits-all' concept toward personalized, on-demand, precision medicine, which will result in smaller, more defined patient populations. In parallel, the global incidence of cancer is rising, which is placing an increasing strain on medical oncology centres, and driving the evolution of oncology pharmacy. Clinical pharmacists can reduce the pressures on other healthcare resources by taking an increased role in patient care and providing a broader range of services. Pharmacists recognize that technological developments will lead to significant changes in pharmacy services, which will require greater integration with other services within the healthcare system. Members of the European Society of Oncology Pharmacy (ESOP) met at the 4th European Conference of Oncology Pharmacy (ECOP) meeting in October 2018 for a symposium entitled The Future of Oncology Pharmacy 2025 . This review summarizes several topics discussed at the meeting, including the future of medicine, oncology and pharmacy healthcare, provides an update on ESOP activities and presents the ECOP 2018 resolution. This position statement outlines the ESOP perspective on how oncology pharmacy will change over the next decade, and how it will respond to these changes to support oncology pharmacists and achieve better outcomes for patients with cancer.